2013
DOI: 10.1038/nchembio.1181
|View full text |Cite
|
Sign up to set email alerts
|

Cold denaturation of a protein dimer monitored at atomic resolution

Abstract: Protein folding and unfolding are crucial for a range of biological phenomena and human diseases. Defining the pathways of protein folding and unfolding is crucial for understanding the origins of a range of biological phenomena and human diseases. However, little is known about the involved structural changes because the species populated during folding and unfolding are highly transient and therefore difficult to grasp by current technology. We have overcome these limitations by a combination of nuclear magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 57 publications
2
32
0
1
Order By: Relevance
“…Notably, phosphorylated SRSF1(RS1) was not as rigid as secondary structure elements in globular proteins. In line with the possibility of significant mobility in structured molecules, we recently showed that the backbone of a well-defined protein folding intermediate remained highly mobile (Jaremko et al, 2013). To take into account the mobility of phosphorylated SRSF1(RS1), we described SRSF1(RpS1) by ensembles of 30 conformers that are in agreement with a large number of NMR observables.…”
Section: Structurementioning
confidence: 93%
“…Notably, phosphorylated SRSF1(RS1) was not as rigid as secondary structure elements in globular proteins. In line with the possibility of significant mobility in structured molecules, we recently showed that the backbone of a well-defined protein folding intermediate remained highly mobile (Jaremko et al, 2013). To take into account the mobility of phosphorylated SRSF1(RS1), we described SRSF1(RpS1) by ensembles of 30 conformers that are in agreement with a large number of NMR observables.…”
Section: Structurementioning
confidence: 93%
“…Therefore, also the possible salt-bridges between the side chains of Glu and Lys stabilizing the four-helices tertiary structure can be excluded. 15 Discussion. The mass spectrometric measurements demonstrate unambiguously that peptides containing a b-aminohydroxamic or an imidazoilo hydroxamic moiety at C-termini formed the supramolecular structures with the compositions corresponding to those of metallacrowns.…”
Section: Nmr Experimentsmentioning
confidence: 96%
“…A tight correlation ( R 2 = 0.921, Fig. B) is obtained between dimer/monomer molar ratio X , a measure of association propensity obtained from average values of hydrodynamic radius , and the interfacial tension. This correlation validates the variational frustration principle and its dynamic steering role in complex formation.…”
Section: Resultsmentioning
confidence: 80%
“…We demonstrate that frustration‐related water polarization steers protein–protein (PP) associations with high specificity and drives the dynamics of complex formation. The validation of these assertions entails contrasting optimally frustrated states with affinity scanning of PP‐interfaces in complexes that assemble to mitigate frustrated hydration of free subunits, and with NMR information on the dynamics of complex formation . Subsequently, we identify the optimal sequence of steps that maximize the mitigation of interfacial tension, funneling complex formation.…”
mentioning
confidence: 97%